The Planning Process of the “WISE ASSIST” Daily Living System for Senior Citizens - Umi Nashwah Mohd Zainiu; Nurdiana Azizan (USIM PRESS, 2024)
Malaysian Journal of Science, Health & Technology (MJoSHT) Volume 10 Issue 1 Page (26-38)